(untitled) (Eurasian Journal of Engineering and Technology, 2023)
Recently, due to the large specific energy costs, it has become impossible to produce competitive products. Reducing the specific consumption of products requires the transfer of electricity to the power supply system with minimal losses. One of the ways to solve this problem is reactive power compensation with the definition of their type, rated power and installation locations.